Pengaruh Stres Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan Pada PT Ultra Prima Abadi (Divisi Formula) Jakarta Barat - Amelia Adnan, Tiara; Tumanggor, Rahmayanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. The purpose of this study was to determine the Effect of Work Stress and Work Conflict on Employee Performance at PT. Ultra Prima Abadi both partially and simultaneously. The method used is quantitative. The sampling technique used was saturated sampling and the sample obtained in this study was 60 respondents. The data obtained were then processed using SPSS statistical software version 26. This analysis includes validity tests, reliability tests, classical assumption tests, simple regression analysis tests, multiple regression analysis tests, correlation and determination coefficient tests, and hypothesis tests t-tests and f-tests. The results of this study are that work stress has a significant effect on job satisfaction with the regression equation Y = 21.957 + 0.282 X1, the correlation value is 0.287, meaning that the two variables have a low relationship. The coefficient of determination value is 8.3%. The hypothesis test obtained t count> t table (2.287> 1.672). Work conflict has a significant effect on employee performance with the regression equation Y = 15.740 + 0.479 X2 correlation value of 0.469 means that the two variables have a moderate level of relationship. The coefficient of determination value is 22%. Hypothesis test t count> t table or (4.049> 1.672). The influence of Work Stress and Work Conflict has a significant effect on employee performance with the regression equation Y = 16.062 + 0.033 X1 + 0.501 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is obtained at 0.470, meaning that it has a strong relationship. The coefficient of determination or contribution of influence simultaneously is 22.1% while the remaining 77.9% is influenced by other factors. Hypothesis test obtained F count> F table or (8.086> 3.162). Keywords: Work Stress, Work Conflict, Employee Performance